ANALISIS MOTIVASI TERHADAP HASIL BELAJAR PESERTA PELATIHAN AKUNTANSI BERBASIS AKRUAL - Raden Yudhy Pradityo (Universitas Pakuan, 2020)
One effort to support the successful implementation of accrual-based government accounting in each reporting entity is training for the development of accrual-based government accounting technical competency. Satisfying learning outcomes are expected to increase the level of success in applying accrual accounting to government. The motivation of the trainees is one of the factors that influence the learning outcomes of the trainees. For this reason, this study aims to examine the effect of training participants' motivation on learning outcomes during training. This research was conducted on training participants for developing the technical capabilities of accrual-based government accounting in the Provincial Government of DKI Jakarta. The results showed that motivational variables affect the learning outcomes of accrual-based accounting training participants. The results of this study can be used as an evaluation material for the organizers of technical capacity building training to be able to increase participant motivation through analysis of participant needs.